IMPLEMENTATION OF AUTHENTIC ASSESSMENT OF THE IMPLEMENTATION OF MERDEKA CURRICULUM IN PAI SUBJECTS AT MA AL-KHAIRIYAH RANCARANJI, SERANG REGENCY - Lismawati, Lismawati; Wasehudin, Wasehudin; Tarihoran, Naf’an; Hilmiyati, Fitri; Oktaviana, Fadilla (Tadrib: Jurnal Pendidikan Agama Islam, 2023)
Knowing the implementation of authentic assessment by PAI teachers in the learning process towards the readiness of implementing the independent curriculum which requires teachers to carry out authentic assessments is the goal to be achieved in this research. Qualitative descriptive is the method used in this research. Data collection through interviews, observation, and documentation. The research sample was taken purposively, namely as many as 6 PAI teachers (Al-Quran Hadith, Fikih, Akidah Akhlak). The results obtained from the research show that there is an influence between the habit of applying authentic assessments on the readiness to implement the independent curriculum. As many as 66.6% of teachers stated that they understood authentic assessment and of the 66.6% of teachers who understood, 25% had not implemented authentic assessment. This is caused by teachers who think that authentic assessment is quite complicated to do and requires a long process that requires it in the long term. This has an impact on the lack of readiness to implement authentic independent curriculum assessments. Teachers who have not carried out authentic assessments feel unprepared if they have to apply authentic assessment to an independent curriculum, if there is no training on an independent curriculum, especially in matters related to authentic assessment